Economy Profile of Guatemala - World Bank Group (World Bank, Washington, DC, 2017)
Doing Business 2018 is the 15th in a series of annual reports investigating the regulations that enhance business activity and those that constrain it. This economy profile presents the Doing Business indicators for Guatemala. Doing Business presents quantitative indicators on business regulation and the protection of property rights that can be compared across 190 economies; for 2018 Guatemala ranks 97. Doing Business measures aspects of regulation affecting 11 areas of the life of a business. Ten of these areas are included in this year’s ranking on the ease of doing business: starting a business, dealing with construction permits, getting electricity, registering property, getting credit, protecting minority investors, paying taxes, trading across borders, enforcing contracts and resolving insolvency. Doing Business also measures features of labor market regulation, which is not included in this year’s ranking. Data in Doing Business 2018 are current as of June 1, 2017. The indicators are used to analyze economic outcomes and identify what reforms of business regulation have worked, where and why.